The Role Of Green Marketing On Millennial Purchase Intentions - Ruspendi Junaedi, I Wayan; Sumartana, I Made; Nyoman Wiratanaya, Gede (Journal of Management, 2023)
The selling of sustainable and eco-friendly goods and services is becoming more and more important in the realm of green marketing and advertising. Such marketing tactics assist them in fulfilling both their financial and environmental obligations. On the other hand, little is known about how green marketing and advertising affect consumer preferences, both directly and indirectly. The extent to which consumer views regarding green marketing and advertising affect their decision to purchase food goods has not been extensively studied. The study used cross-sectional surveys of consumers who use ecologically friendly cosmetics to get around these disparities. When gathering data, a sample strategy is employed. Preliminary results indicate that environmentally friendly marketing has a significant impact on consumers' intentions to make purchases. Conversely, research appears that customers' inclination to purchase is unaffected by ecologically responsible advertising. Three-seven percent of the purchase variable is made up of marketing and green advertising